A Critical Investigation of Technological Pedagogical Content Knowledge (TPACK) of EFL Teachers - Husain, Balqis; Yusuf, Fazri Nur; Sukyadi, Didi (The Indonesian Institute of Science and Technology Research, 2025)
This qualitative study aims to assess the experiences of EFL teachers teaching online regarding TPACK. Four EFL teachers from various school levels were interviewed, observed, and had documents retrieved. The data analysis revealed that EFL teachers from secondary schools were competent in TK, CK, and PK but struggled in TPK, TCK, and TPACK. Despite being competent in TK, they struggled to integrate technology into learning instruction. However, Tertiary EFL teachers were competent in integrating technology into content and learning strategies, which distinguished them from EFL teachers at the secondary school level. The framework for Secondary EFL teachers showed no proportionality between the three core components of TPACK, particularly TK toward PK and CK. In comparison, the framework for tertiary EFL teachers demonstrated that technological, pedagogical, and content knowledge components shared a comparable mastery of competencies.